Rancang Bangun Sistem Informasi Peminjaman Buku Perpustakaan SMP Ibnu Aqil Berbasis WEB - Endriawan, Muhammad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Ibnu Aqil is an educational institution characterized by Islam with the understanding of ahlussunah wal jama'ah, founded by the Haji Agus Salim Bogor Foundation in 1992, amidst the rapid development of information technology, libraries at Ibnu Aqil Middle School in book data collection and book lending are still running manually, for example In borrowing data collection, it is still recorded in books so that it has shortcomings, namely making it difficult for librarians to search for borrower data, checking book availability cannot be done, recording borrowing and returning books often writing errors. Based on the description above, the writer tries to analyze and study the feasibility of the system running at Ibnu Aqil Middle School which the author wrote on a scientific proposal entitled Design and Build Information System for Book Borrowing in the Library of WEB-Based Ibnuaqil Middle School. in the library that can manage book lending and calculate fines automatically so that you can find out the weaknesses that exist in the library to improve the quality of better service to students. The development of this system uses the waterfall method and uses Data Flow Diagrams (DFD) for structured modeling, the programming languages ​​used are PHP, javascript, HTML, CSS, PhpMyAdmin as the database. This information system can make it easier to carry out the transaction process for borrowing books in Ibnu Aqil's library.